Structural and Magnetic Studies of NixCo0.8-xMn0.2Fe2O4 Nanoparticles Prepared via Co-precipitation Rout - Adeela, N.; Maaz, K.; Khan, U.; Iqbal, M.; Hussain, M.; Nisar, A.; Ahmad, M.; Karim, S. (The Nucleus, 2015)
Ni substituted Mn-Co ferrite nanoparticles (NixCo0.8-xMn0.2Fe2O4), with doping content (x) varying from 0 to 0.1, have been synthesized via co-precipitation route. X-ray diffraction reveals the formation of single phase spinel ferrite structure. Fourier transform infrared spectroscopy exhibits presence of two absorption bands appearing at 500-600 cm-1 which are characteristic feature of spinel ferrites. Microstructural analyses were carried out by using scanning electron microscope, transmission electron microscope and energy dispersive X-ray spectroscope which determine the particle size and chemical composition of the synthesized nanoparticles. From TEM results, average particle size was determined to be about 20 nm, which is in good agreement with XRD results. Magnetic results show increase in coercivity and decrease in saturation magnetization with increasing doping concentration.